Altering metabolite distribution at Xenopus cleavage stages affects left–right gene expression asymmetries. Issue 5 (7th April 2021) - Onjiko, Rosemary M.; Nemes, Peter; Moody, Sally A.
Summary: The left–right (L–R) axis of most bilateral animals is established during gastrulation when a transient ciliated structure creates a directional flow of signaling molecules that establish asymmetric gene expression in the lateral plate mesoderm. However, in some animals, an earlier differential distribution of molecules and cell division patterns initiate or at least influence L–R patterning. Using single‐cell high‐resolution mass spectrometry, we previously reported a limited number of small molecule (metabolite) concentration differences between left and right dorsal‐animal blastomeres of the eight‐cell Xenopus embryo. Herein, we examined whether altering the distribution of some of these molecules influenced early events in L–R patterning. Using lineage tracing, we found that injecting right‐enriched metabolites into the left cell caused its descendant cells to disperse in patterns that varied from those in control gastrulae; this did not occur when left‐enriched metabolites were injected into the right cell. At later stages, injecting left‐enriched metabolites into the right cell perturbed the expression of genes known to: (a) be required for the formation of the gastrocoel roof plate ( foxj1 ); (b) lead to the asymmetric expression of Nodal ( dand5/coco ); or (c) result from asymmetrical nodal expression ( pitx2 ). Despite these perturbations in gene expression, we did not observe heterotaxy in heart or gut looping at tadpole stages. These studies indicate that altering metabolite distribution at cleavage stages at the concentrations tested in this study impacts the earliest steps of L–R gene expression that then can be compensated for during organogenesis.